Application of the MELPUFF model to air quality assessment in the industrial area of Huelva (Spain). (1st January 2002) - Acena, B.; Palomino, I.; Martin, F.; Palacios, M.
The mesoscale Lagrangian puff dispersion model (MELPUFF) has been used in air quality assessment in the area of Huelva. The Huelva area is highly industrialised and it is located on the Atlantic coast of southern Spain. The MELPUFF model was applied to obtain monthly-averaged distributions of SO2 and number of probable exceedances per month of the EU air quality standards. The study period corresponds to one year from March 1999 to February 2000. Results of monthly averaged concentrations of pollutants computed by the model were compared with the measured data at the air quality network stations.